Expression of the LRRC52 g subunit (g2) may provide Ca2+‐independent activation of BK currents in mouse inner hair cells. Issue 11 (26th July 2019) - Lang, Isabelle; Jung, Martin; Niemeyer, Barbara A.; Ruth, Peter; Engel, Jutta
Abstract : Mammalian inner hair cells (IHCs) transduce sound into depolarization and transmitter release. Big conductance and voltage‐ and Ca 2+ ‐activated K + (BK) channels are responsible for fast membrane repolarization and small time constants of mature IHCs. For unknown reasons, they activate at around ‐75 mV with a voltage of half‐maximum activation ( V half ) of ‐50 mV although being largely insensitive to Ca 2+ influx. Ca 2+ ‐independent activation of BK channels was observed by others in heterologous expression systems if γ subunits leucine‐rich repeat‐containing protein (LRRC)26 (γ1) and LRRC52 (γ2) were coexpressed with the pore‐forming BKα subunit, which shifted V half by ‐140 and ‐100 mV, respectively. Using nested PCR, we consistently detected transcripts for LRRC52 but not for LRRC26 in IHCs of 3‐wk‐old mice. Confocal immunohistochemistry showed synchronous up‐regulation of LRRC52 protein with BKα at the onset of hearing. Colocalization of LRRC52 protein and BKα at the IHC neck within ≤40 nm was specified using an in situ proximity ligation assay. Mice deficient for the voltage‐gated Cav 1.3 Ca 2+ channel encoded by Cacna1d do not express BKα protein. LRRC52 protein was neither expressed in IHCs of BKα nor in IHCs of Cav 1.3 knockout mice. Together, LRRC52 is a γ2 subunit of BK channel complexes and is a strong candidate for causing the Ca 2+ ‐independent activation of BK currents at negative membrane potentials in mouse IHCs.—Lang, I., Jung, M., Niemeyer, B. A., Ruth, P., Engel, J. Expression of the LRRC52 γ subunit (γ2) may provide Ca 2+ ‐independent activation of BK currents in mouse inner hair cells. FASEB J. 33, 11721‐11734 (2019). www.fasebj.org